PREDICTION OF BLOOD LOSS DURING OPERATIONS USING AI (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This study addresses the issue of predicting bleeding during surgical operations using artificial intelligence (AI) technologies. Based on modern machine learning and deep learning algorithms, patient clinical parameters, laboratory tests, imaging diagnostic data, and factors related to the surgical process are analyzed. AI-based prediction models allow surgeons to identify high-risk cases in advance, minimize blood loss, and increase surgical safety. The results of the study show that the use of artificial intelligence can help to more accurately assess the risk of intraoperative bleeding, support clinical decision-making, and reduce the number of complications.
Keywords: Artificial intelligence, machine learning, surgery, bleeding prediction, medical data analysis, clinical decision support.